IMPLEMENTASI BIMBINGAN DAN PENYULUHAN ISLAM DALAM MENINGKATKAN KUALITAS SPIRITUAL MASYARAKAT MULTIKULTURAL - Suriati, Suriati; Suriyati, Suriyati; Anis, Muh.; Muhlis, Muhlis; Riska, Riska (Universitas Islam Ahmad Dahlan, 2026)
This study aims to examine the implementation of Islamic guidance and counseling (ICC) in improving the spiritual quality of multicultural societies. The background of this research is based on the challenges of social life in Indonesia, which is characterized by cultural, ethnic, and religious diversity, which has the potential to give rise to conflict and spiritual crises. Islamic guidance and counseling is seen as a strategic tool for building community spirituality, strengthening tolerance, and fostering moderate attitudes. This study used a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman model: data reduction, data presentation, and conclusion drawing, with source triangulation for validation. The results show that the implementation of Islamic guidance and counseling includes individual counseling, group counseling, multicultural dialogue, and the use of digital media in da'wah (Islamic outreach). The impact is increased spiritual awareness, strengthened moral values, and the realization of social harmony. This study concludes that Islamic guidance and counseling plays a significant role in building a religious, inclusive, and harmonious multicultural society. Therefore, strengthening the capacity of counselors and institutional support is necessary so that Islamic guidance and counseling can function more effectively in diverse social contexts.